The Impact of Competition on Macroeconomic Performance - Karl Aiginger (Austrian Institute of Economic Research (WIFO), 2008)
This paper investigates to which extent tough competition impacts on the macroeconomic performance of countries. The relation between competition and innovation has been investigated intensely in industrial economics. It started with Schumpeter's hypothesis that monopoly profits were necessary for innovation, leading then to U-curve relationships where innovation was highest for medium-range competition, but lower for very tough competition as well as for a very lax competitive regime. Empirical studies on the growth differences between countries increasingly stress – apart from the usual suspects like investment, R&D, human capital – the role of institutions. They include indicators on regulation, government size, corruption and rule of law, but usually not the degree of competition. Conventional growth theory did not model the impact of competition, but assumed perfect competition. In New Growth Theory, economic growth depends on purposeful and maximising innovation activities, where market structure plays an important role. But this did not result in the inclusion of competition variables into empirical growth equations. We have attempted to narrow this gap by relating 13 indicators of the toughness of competition to macroeconomic performance. We then added these competition indicators to an equation relating macro performance to the standard explanatory variables for economic growth (like investment and R&D). The results indicate that competition plus innovation is a good recipe at the macro level too, probably with similar tensions and non-linearity as at the company level.
Keywords: 330; Competition; Macroeconomic; Performance; Innovation; Wettbewerb; Innovation; Effizienz; Industrieökonomik; Welt